A novel DNA methylation marker to identify lymph node metastasis of colorectal cancer - Yu, Yingdian; Xue, Wenyuan; Liu, Zefeng; Chen, Shang; Wang, Jun; Peng, Quanzhou; Xu, Linhao; Liu, Xin; Cui, Chunhui; Fan, Jian-Bing (Frontiers in Oncology, 2022)
Lymph node metastasis (LNM) of colorectal cancer (CRC) is an important factor for both prognosis and treatment. Given the deficiencies of conventional tests, we aim to discover novel DNA methylation markers to efficiently identify LNM status of CRC. In this study, genome-wide methylation sequencing was performed in a cohort (n=30) using fresh CRC tissue to discover differentially methylated markers. These markers were subsequently validated with fluorescence quantitative PCR in a cohort (n=221), and the optimal marker was compared to conventional diagnostic methods. Meanwhile, immunohistochemistry was used to verify the effectiveness of the antibody corresponding to this marker in a cohort (n=56). LBX2 achieved an AUC of 0.87, specificity of 87.3%, sensitivity of 75.7%, and accuracy of 81.9%, which outperformed conventional methods including imaging (CT, PET-CT) with an AUC of 0.52, CA199 with an AUC of 0.58, CEA with an AUC of 0.56. LBX2 was also superior to clinicopathological indicators including the depth of tumor invasion and lymphatic invasion with an AUC of 0.61and 0.63 respectively. Moreover, the AUC of LBX2 antibody was 0.84, which was also better than these conventional methods. In conclusion, A novel methylation marker LBX2 could be used as a simple, cost-effective, and reliable diagnostic method for LNM of CRC.